An anthropologist among the historians and other essays - Cohn, Bernard S. (Delhi : Oxford University Press, 1987)
On the civilization and socioeconomic conditions of India; articles.
Includes bibliographies.
1
Keywords: India -- Civilization; India -- Social conditions